MR Carotid Plaque Imaging and Contrast-Enhanced MR Angiography Identifies Lesions Associated with Recent Ipsilateral Thromboembolic Symptoms: An In Vivo Study at 3T - DeMarco, J.K.; Ota, H.; Underhill, H.R.; Zhu, D.C.; Reeves, M.J.; Potchen, M.J.; Majid, A.; Collar, A.; Talsma, J.A.; Potru, S.; Oikawa, M.; Dong, L.; et al. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Recent research has suggested the importance of plaque composition to identify patients at risk for stroke. This study aims to identify specific plaque features on 3T carotid MR imaging and CE-MRA associated with recent carotid thromboembolic symptoms in patients with mild/moderate versus severe stenosis. MATERIALS AND METHODS: Ninety-seven consecutive patients (symptomatic, 13; asymptomatic, 84) with 50%–99% stenosis by sonography or CT angiography underwent carotid plaque imaging combined with MRA at 3T. The symptomatic carotid artery or the most stenotic asymptomatic carotid artery was chosen as the index vessel to be analyzed. Plaque features were compared by symptomatic status in patients with mild/moderate (30%–70%) versus severe (70%–99%) stenosis on MRA. RESULTS: Ninety (92.8%) patients had sufficient image quality for interpretation. In 50 patients with mild/moderate stenosis, there were significant associations between the presence of the following plaque characteristics and symptoms: thin/ruptured fibrous cap (100% versus 36%, P = .006) and lipid-rich necrotic core (100% versus 39%, P = .022), with marginal association with hemorrhage (86% versus 33%, P = .055). In 40 patients with severe stenosis, only the angiographic presence of ulceration (86% versus 36%, P = .039) was associated with symptoms. CONCLUSIONS: Several plaque components identified on 3T MR imaging are correlated with recent ipsilateral carotid thromboembolic symptoms. These preliminary results also suggest that associations between plaque characteristics and symptom history may vary by degree of stenosis. If confirmed in larger studies, carotid MR imaging may distinguish stable from unstable lesions, particularly in individuals with mild/moderate stenosis in whom the role of surgical intervention is currently unclear. AUCarea under the curveCEAcarotid endarterectomyCE-MRAcontrast-enhanced MRACE-T1WIcontrast-enhanced T1WICIconfidence intervaln/anot applicableMRAMR angiographyNASCETNorth American Symptomatic Carotid Endarterectomy TrialORodds ratioROCreceiver operating characteristic analysisT1WIT1-weighted precontrast imagingT2WIT2-weighted imagingTIAtransient ischemic attackTOFtime-of-flight